(Almost) a slam dunk: Assessing the experiences and opinions of participants in a National Basketball Association (NBA)-funded dropout prevention program. (October 2017) - Geiger, Tray J.; Amrein-Beardsley, Audrey
Highlights: High school students prized the support received from university student-teachers. Classroom teachers were more positive towards the program than student-teachers. Student-teachers were critical of the program's logistics and planning. Abstract: Researchers conducted an evaluation of participants' perceptions of a dropout prevention program − the NBA High School program − involving a National Basketball Association (NBA) team, a high school located in downtown [City], and the College of Education (COE) at the local State University (SU). The program targeted "at-risk" high school students while utilizing student-teachers as tutors and mentors. Researchers utilized mixed methods to assess student, student-teacher, and high school teacher participants' experiences with and opinions of the program. Researchers found (1) students enjoyed the program, especially given the involvement of the student-teachers; (2) students believed the program helped improve their grades; (3) student-teachers enjoyed working with their students, although student-teachers found some of the expectations surrounding their positions and roles as tutors/mentors within the high school to be unclear and frustrating; (4) high school teachers felt significantly better about the program than the student-teachers; and (5) overall, all sets of respondents categorically supported the program and its benefits. Findings indicated that the involvement of mentors or role models matters to students, and clear and organized logistics, planning, and communication are integral for program success.